General agreement... [between] His Majesty's Government in the United Kingdom and Petroleum Development (Oman and Dhofar) Limited - Wakely, Leonard Day; Symon, Alexander Colin Burlington (British Library, 1938)
The file is concerned with an agreement between His Majesty's Government in the United Kingdom and Petroleum Development (Oman and Dhofar) Limited, which relates to the oil concession agreed between the company and the Sultan of Muscat and Oman, Sa‘īd ibn Taymūr Āl Bū Sa‘īd, in respect of the district of Dhofar. The agreement outlines the terms and conditions, laid down by the British Government, regulating the operation of the company in Dhofar. The agreement is signed by Leonard Day Wakely, Deputy Under-Secretary of State for India, on behalf of His Majesty's Government, in the presence of Sir Alexander Colin Burlington Symon, the Assistant Principal for the Political Department in the India Office. It is also sealed by the petroleum company.
Genre: Archival file
Keywords: Relations – Oman – Royaume-Uni

MEMORANDUM (a) The Sultanate of Muscat and Oman. (b) His Highness Sultan Saiyid Said bin Taimur - East India Company (1938)
The file consists of a memorandum in two parts. The first part provides information about the Sultanate of Muscat and Oman in eight sections, entitled, 'Territory', 'Historical', 'Physical Features', 'Climate', 'Population', 'Products and Trade', 'Religion' and 'Government'. The second part describes and gives a brief biography of His Highness Sultan Saiyid Said bin Taimur, and outlines the extent of British influence upon him.
Genre: Archival file
Keywords: Relations – Oman – Royaume-Uni